(untitled) (Fiep Bulletin - online, 2015)
This study aims, after reviewing the recommendations about the physical exercise to the treatment of osteoporosis, to verify the changes on the bones density in a woman with posterior osteoporosis to the introduction of a physical exercise program in a conventional treatment of osteoporosis only with medication, diet and walks without professional guidance, whose individual of this research is a woman who will undergo a physical exercise program in the osteoporosis treatment, following the recommendations to this special group. The bone mineral density (BMD) , the percentage of the mineral content related to the young adult and the percentage of the mineral content for the group age were analyzed . The annual exams from 2007 to 2014 were analyzed, therefore the oriented exercise program was introduced in September 2010 and with a specific and regular weightlifting program three times a week. The weightlifting program consisted of three series of exercises to each muscular area, in a single training to be done on Mondays, Wednesdays and Fridays. The load was determined by repetition established in 12 times to each training section with emphasis to the progressive increase on the impact on the Skeletal System. It was determined that in each training section, an interval treadmill training, alternating jog trot and a walk. The pathology picture of the volunteer had relevant results. This way, the results obtained in this study allow the conclusion that the applied physical exercise program was effective to the increase of the bone mineral density and the percentage of the mineral content to the age group, becoming its classification normal.